PENGARUH DISIPLIN KERJA, MOTIVASI KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA AMARTHA MIKRO FINTECH DI SUMBAWA, NUSA TENGGARA BARAT - Yaturroi, Ida; Sri Wahyulina (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the significance of: (1) Work discipline on employee performance, (2) Work motivation on employee performance, and (3) Organizational culture on employee performance at Amartha Mikro Fintech Sumbawa (West Nusa Tenggara). This study is an associative study with a quantitative approach using a census technique, with all 33 employees serving as respondents. Data collection techniques were conducted through questionnaires, interviews, and documentation. Data analysis used multiple linear regression with the help of IBM SPSS version 26. The results show that: (1) Work discipline has a positive and significant effect on employee performance, (2) Work motivation has a positive and significant effect on employee performance, and (3) Organizational culture has a positive and significant effect on employee performance. Simultaneously, all three variables significantly influence employee performance.